Evaluating a model program for improving law enforcement officers’ perceptions of and interactions with youth in a diverse urban setting - Burke, Stephanie C. (Psychology, crime & law, 2026)
Negative and, at times, violent encounters between police and youth have received increasing attention in recent years, leading to calls for more targeted training of law enforcement. In Pennsylvania, legal stakeholders collaborated to create a manualized curriculum training designed to educate law enforcement on developmentally appropriate ways to interact with youth and generate conversation between police and young people (particularly youth of color) with the goals of reducing stereotyping and improving relationships between these two groups and, ultimately, reducing racial and ethnic disparities in youth arrest rates. The current study evaluated change in law enforcement perceptions from 24 trainings conducted in Philadelphia – a city populated predominantly with residents of color – which included both formal and informal interactions with young, predominantly Black, volunteers. Data from the Police-Youth Engagement Survey, completed both before and after trainings by 1,344 police recruits, indicated curriculum acceptability and recruits’ willingness to use information from the training in their future interactions with youth. Recruits’ attitudes towards youth and their perceptions of the relationship between police and young people also significantly improved. Results indicate that this training may be a promising initial intervention for improving interactions between law enforcement and youth, including youth of color.